Peningkatan Perekonomian Peternak Melalui Pengolahan Limbah - Widodo, Nur; Farhan, Naufall; Romadhoni, Syahrul; Afif, M.; Darril, Fathan; Dwi, Alvian; Prasetiyo, Dhani (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
Bondowoso Regency is a center for sheep farming in Indonesia. The establishment of a sheep breeding center in Indonesia has resulted in a large sheep population in Bondowoso Regency. Sheep farming not only produces meat, but also by-products such as wool and waste. Waste that is not utilized properly can cause environmental pollution. One of the villages in Bondowoso Regency which has many sheep farms is Prajekan Kidul Village. The PPK Ormawa Team of the Breeder Study Program Student Association (HIMAPROSTER) Jember University empowered farmers in processing sheep manure waste into solid organic fertilizer. The methods used in this program are focus group discussions, socialization, counseling, practice, mentoring and activity evaluation. After this activity can provide a solution to the problem of livestock waste waste in Prajekan Kidul Village. It is also able to improve the economy of farmers thanks to the sale of solid organic fertilizer.